New record of Megalestes gyalsey Gyeltshen, Kalkman & Orr, 2017 (Zygoptera: Synlestidae) from India, with first description of female and larva - Payra, Arajush; Dawn, Prosenjit; Subramanian, K. A.; Deepak, C. K.; Chandra, Kailash; Tripathy, Basudev (Zootaxa, 2021)
Megalestes gyalsey Gyeltshen, Kalkman & Orr, 2017 is recorded for the first time from India, extending the known geographic range of the species. This report is based on the collection of 5 individuals (4 males, 1 female) from Jang waterfall, Tawang, Arunachal Pradesh and 2 males from Neora Valley National Park, Kalimpong district, West Bengal. The female of M. gyalsey is described for the first time with notes on the variation in the male. A probable larva of the species is also described and illustrated.